Chemical Composition and Antimicrobial Activity of Artemisia tournefortiana Rchb. Essential Oil - Kazemi, M.; Akhavani, S. (Asian Journal of Chemistry, 2013)
The water distillation of the aerial parts of Artemisia tournefortiana has been analyzed by a combination of GC-FID and GC/MS in early flowering stage. The main components of Artemisia tournefortiana were (Z)-nerolidol (22.4 %), b-caryophyllene (15.6 %) and santolina triene (10.1 %). The antimicrobial activity of the oil was determined against eight bacteria and two fungi strains. The oil was active against all the tested strains. The oil has shown maximum zone of inhibition to Staphylococcus aureus. Staphylococcus aureus was the most sensitive microorganisms to the essential oil (having MIC value 125 and MBC value 250 μg/mL). The potent antimicrobial activity of oil could be associated with terpenes alcohols.